Mega-events and modernity : Olympics and expos in the growth of global culture - Roche, Maurice (Routledge, 2000)
Explores the social history and politics of 'mega-events' from the late 19th century to the present. Case studies: 1936 Berlin Olympics, 1992 Barcelona Olympics, 1851 Crystal Palace Expo. A thoroughly new and ground-breaking analysis.